Reconstruction of feeding behaviour and diet in Devonian ctenacanth chondrichthyans using dental microwear texture and finite element analyses - Merle Greif; Ivan Calandra; Stephan Lautenschlager; Thomas M. Kaiser; Mohammed Mezane; Christian Klug (Royal Society Open Science)
Devonian ctenacanth chondrichthyans reached body sizes similar to modern great white sharks and therefore might have been apex predators of the Devonian seas. However, very little is known about the diet and feeding behaviours of these large ancestral sharks. To reconstruct their ecological properties, teeth of the large Famennian (Late Devonian) chondrichthyan Ctenacanthus concinnus from the Anti-Atlas, Morocco, were analysed. The teeth show strong tooth wear with deep horizontal as well as vertical scratches. Dental microwear texture analysis, a well-established method for the reconstruction of diet and commonly used in terrestrial vertebrates, was applied for the first time, to our knowledge, to Palaeozoic vertebrates in this study. Furthermore, finite element analysis was performed to test the biomechanical properties of the teeth. By combining both analyses, as well as palaeoenvironmental data and tooth morphology, we demonstrate that the results from only one method can be insufficient and misleading. Ctenacanthus concinnus most likely was an opportunistic feeder like many modern sharks. Direct evidence and the results of our analyses suggest that Ctenacanthus fed on ectocochleate cephalopods, other chondrichthyans and further vertebrates using a combination of head movements including lateral head shaking to cut large prey items.